Enantioselective synthesis of planar chiral ferrocenes via palladium-catalyzed annulation with diarylethynes - Shi, Yan-Chao; Yang, Rong-Fei; Gao, De-Wei; You, Shu-Li (Beilstein Journal of Organic Chemistry, 2013)
When Boc-L-Val-OH was used as a ligand for the enantioselective Pd(II)-catalyzed annulation of N,N-substituted aminomethyl ferrocene derivatives with diarylethynes, ferrocenes with planar chirality could be achieved with excellent enantioselectivity (up to 99% ee).
Keywords: annulation; asymmetric catalysis; C–H activation; ferrocene; palladium; planar chirality